Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Rokok Gudang Garam Signature - Nurul Azmi; Anfasha Bahtiar Yusuf (Journal of Management and Economics Research, 2022)
The cigarette industry in Indonesia is a very high contributor to state revenue. The cigarette industry in Indonesia can be detrimental to public health, but on the other hand the cigarette industry has a very large economic role. One of the companies engaged in the cigarette industry is PT. Gudang Garam which was founded by Surya Wonowidjojo in the City of Kediri 26 June 1958. PT. Gudang Garam produces a number of popular cigarette brands in Indonesia such as Gudang Garam Signature. The analytical method in this study used quantitative primary data, the test stages carried out were: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test (partial), F test (simultaneous) and coefficient test determination (R2). The data used in this study used a questionnaire instrument, and the valid data that was collected was 100 respondents with the criteria of consumers who had purchased Gudang Garam Signature Cigarettes. The testing tool used is SPSS 26. The results of the t-test (partial) show that partially the product quality variable has a significant effect on purchasing decisions, and the price variable has no significant effect on purchasing decisions. Based on the results of the F test (simultaneous) research, it shows that the product quality and price variables simultaneously influence purchasing decisions